Centrifuge modelling of piled embankments - Aslam, Raveed (2008)
It is becoming increasingly necessary to construct on land that was previously considered inappropriate for construction, such as soft clay. The properties of soft clay make it highly compressible and low in shear strength, meaning that bearing capacity failure and excessive settlement are of concern.